CONGENITAL PSEUDOARTHROSIS TIBIA IN CHILD WITH NEUROFIBROMATOSIS TYPE 1 TREATED WITH THE COMBINED VASCULARIZED FIBULAR GRAFT AND ELASTIC STABLE INTRAMEDULLARY NAIL (ESIN) - Sulis Bayusentono; Trixie Brevi Putri (Journal Orthopaedi and Traumatology Surabaya)
Background: CPT is a disorder characterized by nonunion tibial fracture that occurs spontaneously or after trivial trauma. Therapy usually includes surgical management and aims to gain lifetime bony union, avoid leg length discrepancy, and to prevent mechanical axis deviation, surrounding soft tissue lesion, joint stiffness, and pathological fracture. CPT remains to be a challenging orthopedic issue due to the difficulty to gain and to maintain the union and functional limb. The combined VFG and ESIN is one of our preferred method in Surabaya.